Revitalizing "Forgotten" African American Cemeteries - Ransone, Rachel K (East Carolina University, 2021)
The degradation, abandonment, and "forgetting" of African American cemeteries have become chronic issues throughout the Southern United States. At their base, these spaces are examples of manipulated landscapes and represent a long history of minimization as the result of an imagined history via the influence of Lost Cause ideology- a negationist ideology which continues to affect the visibility of African American heritage spaces and their contribution to American history. In order to mitigate this manipulation and preserve both historic and contemporary cemetery spaces from further decline, plans for revitalization need to be implemented while simultaneously considering the various terminological, economic, political, and social issues/considerations that are a result of this manipulation. Examples across the South further emphasize the ambiguities of addressing one-sided representations of heritage, culture, and history within the landscape. A current project being conducted by East Carolina University's Department of Anthropology on a "forgotten" African American cemetery in Ayden, North Carolina serves as a model of action for similar projects seeking to mitigate manipulation and reintroduce these cemeteries into their communities.
Keywords: Lost Cause Ideology; Imagined Histories; African American cemeteries--Southern States; United States--History--Civil War, 1861-1865; Southern States--Civilization; Collective memory--Southern States